Feminine Face of God - Arickappalil, Isaac (Asian Horizons, 2009)
The gender of God attracts attention and has relevance only in an anthropological context. We, sexual beings, cannot imagine or want God to remain asexual. hence the confltct. Prof. Isaac Arlckappalil skilfully brings to our attention the social, cultural, and political contexts in which the Sacred Scriptures were written and the necessity of proper exegetical study to understand and appreciate meanings they aspire to convey. Moreover, along with the change in milieu the Sacred Scriptures demand reconstruction and retelling so that the letters may not asphyxiate and exterminate the spirit that they enclose and try to communicate. He also proposes the posstbtllty of advancing a feminine pneumatology which hitherto remains untapped especially in the Western theological Circle.